1989
DOI: 10.1002/bms.1200180706
|View full text |Cite
|
Sign up to set email alerts
|

Identification and determination oftert-alkylphenols in carp from the trenton channel of the Detroit River, Michigan, USA

Abstract: Whole carp from the Detroit River were analyzed by gas chromatographic mass spectrometry. Seven tertiary alkyl phenols (tert-pentylphenols, tert-butyl-tert-pentylphenols, a di-tert-pentylphenol and a tri-tert-pentylphenol) and eight chlorinated derivatives of these compounds were identified from their mass spectra and confirmed with synthesized authentic standards. 2,4-Di-tert-pentylphenol was the most abundant of these compounds; in one fish sample, its concentration was about 140 ppm. The same alkyl phenols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…The contribution of APEs and alkylphenols to the xenoestrogen burden of humans is unknown; however, it has been reported that these chemicals are present in sewage outlets in concentrations sufficient to feminize sentinel fish (38). Alkylphenols accumulate in river sediment and in the fat of exposed fish (39 In addition to the estrogenic alkylphenol antioxidants described above, we found that BHA was estrogenic. BHA is a widely used antioxidant; because it controls oxidation of short-chain fatty acids such as coconut oil (40).…”
Section: Animal Bioassays and The E-screen Assay: Differences And Simmentioning
confidence: 48%
“…The contribution of APEs and alkylphenols to the xenoestrogen burden of humans is unknown; however, it has been reported that these chemicals are present in sewage outlets in concentrations sufficient to feminize sentinel fish (38). Alkylphenols accumulate in river sediment and in the fat of exposed fish (39 In addition to the estrogenic alkylphenol antioxidants described above, we found that BHA was estrogenic. BHA is a widely used antioxidant; because it controls oxidation of short-chain fatty acids such as coconut oil (40).…”
Section: Animal Bioassays and The E-screen Assay: Differences And Simmentioning
confidence: 48%
“…It remains to be determined whether OP in the environment is absorbed in sufficient amounts and for sufficient lengths of time to pose a threat to wildlife and humans. It has been reported that concentrations of 2,4-di-tert-pentylphenol, a related alkylphenol, were in the 10 -3 M range in fat tissue in carp in the Detroit River's Trenton Channel [21]. This concentration was greater than that in the water or water sediment, suggesting not only that the alkylphenol was absorbed by the fish but also that it bioaccumulated in the fat tissue.…”
Section: Discussionmentioning
confidence: 88%
“…These degradation products, nonylphenols, showed estrogenic effects. Alkylphenols are present in certain sewage outlets in concentrations sufficient to feminize certain fish species like trout and carp 3,4 . The in vivo estimated concentration of octylphenols (and consequently others alkylphenols, as nonylphenol) responsible of vitellogenin induction in rainbow trout is between 1-10 µg L -1 and in male roach is 10-100 µg L - 1 5 .…”
Section: Introductionmentioning
confidence: 99%